Digital Clubbing Is Associated with Higher Serum KL-6 Levels and Lower Pulmonary Function in Patients with Interstitial Lung Disease - Kazushige Shiraishi; Torahiko Jinta; Naoki Nishimura; Hiroshi Nakaoka; Ryosuke Tsugitomi; Kohei Okafuji; Atsushi Kitamura; Yutaka Tomishima; Gautam A. Deshpande; Tomohide Tamura (Canadian Respiratory Journal)
Background. Although digital clubbing is a common presentation in patients with interstitial lung disease (ILD), little has been reported regarding its role in assessing patients with ILD. This study evaluated patients with ILD for the presence of clubbing and investigated its association with clinical data. Methods. We evaluated patients with ILD who visited the teaching hospital at which the study was conducted, between October 2014 and January 2015. Clubbing, evaluated using a Vernier caliper for individual patients, was defined as a phalangeal depth ratio > 1. We examined the association of clubbing with clinical data. Results. Of 102 patients with ILD, we identified 17 (16.7%) with clubbing. The partial pressure of oxygen in arterial blood was lower (65.2 ± 5.9 mmHg versus 80.2 ± 3.1 mmHg; p=0.03), serum Krebs von den Lugen-6 (KL-6) levels were higher (1495.0 ± 277.4 U/mL versus 839.1 ± 70.2 U/mL; p=0.001), and the percent predicted diffusing capacity of carbon monoxide was lower (50.0 ± 6.0 versus 73.5 ± 3.1; p=0.002) in these patients with clubbing. Conclusions. Patients with clubbing had lower oxygen levels, higher serum KL-6 levels, and lower pulmonary function than those without clubbing.